The Effect of Dzikir Intensity on Self-Control in Psychology Students - Cholili, Abd. Hamid; Achmad Mubarok; M. Yogi Anggoro; Shafira Angelia Putri; Muhammad Mubasysyir Munir (MADINAH, 2024)
Based on the results of a questionnaire distributed by researchers, it is known that 63% of students do not know how to control themselves. An interview with one of the UIN Malang students with the initials YH said that he already knew about self-control, but had not been able to apply it because he had not found the right method of self-control. Therefore, this research aims to determine the effect of dhikr intensity on students' self-control. This research uses a quantitative design with a self-control scale instrument referring to Averill's self-control theory with 16 items. The dhikr intensity scale refers to Makmun's theory, which has a total of 15 statement items. Data analysis uses the simple regression analysis method. The results of the research show a significance level of 0.00, which means p = 0.000 (p < 0.01), meaning that there is a significant influence between the intensity of dhikr on self-control in students and the R Square value of 0.402, This means that the intensity of dhikr can influence students' self-control by 40.2%. The results of this research also provide an illustration that dhikr done istiqomah can improve a person's self-control.